PRODUK PEMIKIRAN HUKUM ISLAM DI INDONESIA KONTEKSTUALISASI SYARIAT DALAM REALITAS SOSIAL DAN BUDAYA - Umar, Hasbi; Bafadhal, Husin; Khairul, Mohd; Amir, Mirna Novita (YUSTISI, 2026)
Islamic law in its history, was applied in the first year of the hijri in Medina by the Prophet Muhammad (peace be upon him), on the basis of the constitution of the Charter of Medina. In the muqaddimah it is written, that the Charter of Medina is a product of Islamic legal thought, if reviewed from the social history of Islamic law, then its growth and development began from the time of the Prophet (peace be upon him) until now, the change in Islamic law is also influenced by the progress and plurality of socio-cultural and political in a society. In this study, the author uses the Library Research method, which contains theories that are related to research problems. The result of this research is that Islamic Law in Indonesia has become an institutionalized institution including jurisprudence, fatwa, jurisprudence, and laws where its formation is a process of contextualization that is closely related to the social dynamics and local wisdom of Indonesian society. Following the methodological tradition of classical mujtahid scholars, this legal product consistently integrates local cultural values; Local wisdom is even recognized as a binding order. This makes Indonesian Islamic law, especially on the issue of marriage and inheritance, adaptive and responsive, showing a deep appreciation for the social development of the community over time.